Convalescent troponin and cardiovascular death following acute coronary syndrome. Issue 22 (23rd July 2019) - Adamson, Philip D; McAllister, David; Pilbrow, Anna; Pickering, John William; Poppe, Katrina; Shah, Anoop; Whalley, Gillian; Ellis, Chris; Mills, Nicholas L; Newby, David E; Pemberton, Chris; Troughton, Richard W; et al.
Abstract : Objectives: High-sensitivity cardiac troponin testing is used in the diagnosis of acute coronary syndromes but its role during convalescence is unknown. We investigated the long-term prognostic significance of serial convalescent high-sensitivity cardiac troponin concentrations following acute coronary syndrome. Methods: In a prospective multicentre observational cohort study of 2140 patients with acute coronary syndrome, cardiac troponin I concentrations were measured in 1776 patients at 4 and 12 months following the index event. Patients were stratified into three groups according to the troponin concentration at 4 months using the 99th centile (women>16 ng/L, men>34 ng/L) and median concentration of those within the reference range. The primary outcome was cardiovascular death. Results: Troponin concentrations at 4 months were measurable in 99.0% (1759/1776) of patients (67±12 years, 72% male), and were ≤5 ng/L (median) and >99th centile in 44.8% (795) and 9.3% (166), respectively. There were 202 (11.4%) cardiovascular deaths after a median of 4.8 years. After adjusting for the Global Registry of Acute Coronary Events score, troponin remained an independent predictor of cardiovascular death (HR 1.4, 95% CI 1.3 to 1.5 per doubling) with the highest risk observed in those with increasing concentrations at 12 months. Patients with 4-month troponin concentrations >99th centile were at increased risk of cardiovascular death compared with those ≤5 ng/L (29.5% (49/166) vs 4.3% (34/795); adjusted HR 4.9, 95% CI 3.8 to 23.7). Conclusions: Convalescent cardiac troponin concentrations predict long-term cardiovascular death following acute coronary syndrome. Recognising this risk by monitoring troponin may improve targeting of therapeutic interventions. Trial registration number: ACTRN12605000431628;Results.